2021
DOI: 10.1111/jth.15221
|View full text |Cite
|
Sign up to set email alerts
|

PAR1 regulation of CXCL1 expression and neutrophil recruitment to the lung in mice infected with influenza A virus

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…In contrast, PAR1 reduces TLR3-NFkB inflammation but enhances TLR3-IFNb responses (Figure 12) (8,23,36,43,48). In line with this proposed receptor interaction, we have recently shown that the absence of PAR1 leads to increased proinflammatory CXCL1 expression and increased BALF neutrophil numbers which were associated with higher mortality compared to WT mice (26).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In contrast, PAR1 reduces TLR3-NFkB inflammation but enhances TLR3-IFNb responses (Figure 12) (8,23,36,43,48). In line with this proposed receptor interaction, we have recently shown that the absence of PAR1 leads to increased proinflammatory CXCL1 expression and increased BALF neutrophil numbers which were associated with higher mortality compared to WT mice (26).…”
Section: Discussionmentioning
confidence: 63%
“…Cellspecific PAR2 deficient mice were generated by crossing female Par2 fl/fl with male Par2 fl/fl mice expressing Cre recombinase in a cell type-specific manner. To generate mice with Par2 deleted in lung EpCs we used the surfactant protein C (SPC) promoter (Par2 fl/fl ;SPC Cre+ mice) (26,27). The Par2 gene was deleted in the myeloid lineage (monocytes/macrophages and neutrophils) using the lysosomal M (LysM) promoter (Par2 fl/fl ;LysM Cre+ ) (26,(28)(29)(30)(31).…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…To delete PAR1 in CFs (PAR1ΔCF), we used mice expressing Cre recombinase under the transcription factor 21 (TCF21) obtained from Dr. Tallquist 34 . Female PAR1 fl/fl mice 35 , 36 were crossed with male Cre-expressing mice to generate PAR1 fl/fl ;Mlc2v Cre and PAR1 fl/fl ;TCF21 Cre-ERT2 . To activate TCF21 Cre-ERT2 expression 34 , 37 in PAR1 fl/fl ;TCF21 Cre-ERT2 mice, 6 week old mice were gavaged with 2 mg of tamoxifen (Sigma-Aldrich, St. Louis, MO, USA) for 5 consecutive days and then mice used 5 days later.…”
Section: Methodsmentioning
confidence: 99%
“…Variations in input RNA levels and reaction efficiency was corrected against 18S rRNA (4310893E, Applied Biosystems). All RT-PCR reactions were performed with the SSoFast Advanced Universal Supermix in a Bio-Rad cycler (Bio-Rad Laboratories, Hercules, CA, USA) as described elsewhere 36 , 41 .…”
Section: Methodsmentioning
confidence: 99%